Sense of Coherence and Adherence to Self-Care in People with Diabetes: Systematic Review and Meta-Analysis - María del Carmen Vega-Martínez; Catalina López-Martínez; Rafael Del-Pino-Casado (Nursing Reports)
Background/Objectives: Self-care in people with diabetes requires constant physical and emotional effort, which can be a barrier to adhering to the care plan. The sense of coherence (SOC) might play a role in self-care. This study aimed to examine the relationship between sense of coherence and self-care in people with Diabetes Mellitus. Methods: A systematic review with narrative synthesis (14 studies) and with meta-analysis (seven studies) was conducted. We searched PubMed, CINAHL, PsychInfo and Scopus up to June 2025. We included original studies that assessed the relationship between SOC and self-management in people with diabetes and reported the correlation coefficient or other compatible statistic. Selection bias (probabilistic vs. non-probabilistic), classification bias (validity and reliability of the instrument) and confounding (control of sex, age and type of diabetes) were evaluated. The meta-analysis used a random-effects model with sensitivity and subgroup analyses to assess robustness. Results: Fourteen studies with 9800 participants (type 1 or 2 diabetes) were included. Of the studies, eight used probability sampling, only one had classification bias risk, and three had low bias risk. A positive, moderate association was found between SOC and adherence to self-care (r = 0.32; 95% confidence interval (CI): 0.29, 0.35; N = 3985; average per study: 569.3). Limitations: a small number of studies; all were descriptive and cross-sectional. Conclusions: A sense of coherence may play a relevant role in improving adherence to the self-care plan in people with type 1 or 2 diabetes.